Educational Planning Through Sharia Insurance for Gold Generation of Indonesia in 2045 - Fitria Nur Ngaini (Journal of Contemporary Islamic Education, 2022)
The Central Statistics Agency (BPS) reports that the Indonesian adult population has a low interest in continuing education, due to the cost factor. This is the impact of the Indonesian population who do not have a good education cost plan. In fact, in 2045, Indonesia is predicted to have a golden generation because of the demographic bonus, which is 70 percent of the population is of productive age. Therefore, an effort is actually needed to prepare for the cost of education to a higher level, namely Sharia Education Insurance. Based on this background, this paper will analyze the impact of education planning through Islamic education insurance for Indonesia Emas 2045. This research is a literature study that collects data from primary and secondary literature, then describes it qualitatively. This paper argues that, the government must make improvements to the education sector, workforce training, industrial structure, transformation of the workforce, to improving the labor supply chain to welcome Indonesia 2045. In addition, the government must also maintain the employment sector which will increase in 2022, namely agriculture, forestry and fisheries, as well as fixing jobs in the service and commuting sectors which have experienced a decline. In order to achieve these improvements, previous improvements must be made in education planning through Islamic education insurance, because if this sector is not improved, the demographic bonus will only increase the number of unemployed.